Inventarisasi dan Identifikasi Jenis Tumbuhan Pengendali Hama di Kecamatan, Kabupaten Rembang, Provinsi Jawa Tengah - Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 2001)
The economic crisis also hit hard the agricultural sector, as production inputs such as synthetic chemical pesticides and fertilizers became expensive and at times hard to get. But the ingenious and innovative thinking of the farmers were sometimes proven invaluable. They look back at the practices inherited from their ancestors: using plant materials as botanical pesticides as well as compost. While earlier the farmers were told that botanicals' use promotes safer environment and cleaner products, later they chose the alternative with more economical consideration. Unfortunately they have little, if available, records and notes regarding these promising plant materials. Not much have been done in the past to identify and record the kinds of plant and plant materials with pesticidal properties. This study was done based on this premise. Rembang regency in north-eastern Central Java is a region with diverse area, starting from low coastal land to woody tropical hills. The farmers living in the area has long known the use of botanicals, but not as intensive as during the present (the year 1998–2000). The systematic and thorough inventory and identification of such botanicals, however, has yet to be done. Therefore a survey was conducted in Kecamatan Pamotan, Rembang regency, by attending the village gathering, talking to elders and leaders, and through snowball effect method collecting information from farmers who use botanicals to protect their crops. Visit to the field and woods to identify the plants were also carried out. The result is records on the kinds, relative number, the use and other important facts which may serve as the basis for further improvement of these environmentally friendly practices.